PERCEPTIONS OF GASTROENTEROLOGISTS AND ENDOSCOPISTS ON ARTIFICIAL INTELLIGENCE: A QUALITATIVE STUDY - Khan, Jibran Umar Ayub; Khan, Tanweer; Mahmood, Sidra; Inayat, Adnan; Shah, Syed Abdul Ahad Ali; Shah, Azhar Zahir (Khyber Journal of Medical Sciences, 2025)
Objective: To explore the perceptions of gastroenterologists and endoscopists on artificial intelligence Methodology: This study was conducted in main teaching hospitals of Peshawar and interviews were taken from 8 consultant gastroenterologists well versed in their fields Qualitative study design with interpretative phenomenology analysis (IPA) as methodology was used. Well informed consent was taken from the participants. Participants were explained the purpose of the study. Semi-structured interviews were conducted in offices of the consultants and did last approximately 30 min each. Answers will be recorded by note taking or audio taping. Interview was taken until a theoretical saturation was achieved and that there were no new concepts emerging from additional interviews. Results: While there was a growing interest in AI, its practical implementation in clinical settings was limited. Over reliance on artificial intelligence will lead to reduction in critical thinking and brain storming abilities of trainees. AI was viewed as having both positive and negative impacts on medical training. Positive aspects include improved diagnostic accuracy, enhanced procedural efficiency, and streamlined research capabilities. Key challenges to AI implementation included financial constraints and a lack of awareness. The high cost of AI software and hardware, coupled with limited budgets, posed significant barriers to adoption. Conclusion: In conclusion, while there is a growing interest in AI among gastroenterologists, significant challenges remain in terms of implementation and adoption. Addressing these challenges will require a multi-faceted approach, including financial investments, targeted training programs, and a supportive regulatory environment.